Toxicity of Plant-Based Insecticide Extracts of Tobacco Stem (Nicotiana tabacum L.), Babadotan Leaves (Ageratum conyzoides L.) and a Combination of These to Control Crocidolomia pavonana F. Larvae - A’isyah Putri Latifatuzzahro’; Mohammad Hoesain; Fariz Kustiawan Alfarisy (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
Crocidolomia pavonana is one of the pests that attacks the Brassicaceae family. The larvae of C. pavonana can eat cabbage plants until they are able to reduce production by 79.81%. One of the solutions to control this pest is to use plant-based insecticides. This study aims to determine the toxicity of tobacco stem extracts, babadotan leaves and a combination of the two against C. pavonana. Each extract was tested to instar III C. pavonana larvae by leaf dip method. At 96 hours after treatment, babadotan extract (17%) had a mortality value of 93.33%, while tobacco extract (30%) had a mortality value of 93.33%. Babadotan extract had a lower LC50 than tobacco extract of 6,710 and 10,640, respectively. Meanwhile, the combination of Ac:Nt (3:5) had the best mortality and LC50 values, which were 96.67% and 5.245. These values indicate that the combination of extracts is more toxic than single ingredients. Based on the combination index, the combination of Ac:Nt (3:5) at the LC50 and LC95 levels is weak synergistic. Thus, the single-ingredient treatment of babadotan extract was more toxic than the tobacco stem extract, but the combination treatment of Ac:Nt (3:5) was more toxic than the treatment of single extract.